Uterine Preservation in a Young Woman with Pelvic Organ Prolapse: An Interventional Case Report - Ekarini Aryasatiani; Raymond Surya Tan (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2026)
Introduction: The prevalence of pelvic organ prolapse (POP) is approximately 2 - 20% in women under the age of 45 years. Uterine preservation appears promising for young patients who have not completed childbearing. Sacrohysteropexy is preferred when uterine preservation is desired, with cure rates of 91-100%. This report describes a woman with pelvic organ prolapse who wished to preserve her uterus and underwent abdominal sacrohysteropexyCase Illustration: A 42-year-old woman, P2A0, presented with a bulging mass following vaginal birth, noted 6 months before admission. She continues to menstruate regularly, and her husband hopes to have another child. On Pelvic Organ Prolapse Quantification (POP-Q) examination, she was diagnosed with 4th grade uterine prolapse, 3rd grade cystocele, and 3rd grade rectocele. She decided to preserve her uterus with abdominal sacrohysteropexy. At one-month follow-up, the patient was satisfied with the procedure and reported no further complaint of mass bulging.Discussion: Sacrohysteropexy is a promising procedure to preserve the uterus, with success rates of up to 90% at three to five years. Use of mesh may be associated with the risk of infection and mesh erosion into the vagina. Recurrence is usually caused by pelvic floor weakness, with a rate of 16.7% in a local study.Conclusion: Abdominal sacrohysteropexy is a safe procedure for POP in young women who wish to preserve the uterus, provided it is performed carefully.Preservasi Uterus pada Prolaps Organ Panggul Wanita Muda: Sebuah Laporan Kasus Intervensi AbstrakPendahuluan: Prevalensi prolaps organ panggul (POP) terjadi sekira 2 - 20% pada wanita di bawah 45 tahun. Konservasi uterus tampak menjanjikan pada pasien usia muda dan masih menginginkan anak. Sakro histeropeksi menjadi salah satu pilihan, preservasi uterus dapat mencapai 91-100%. Kasus ini melaporkan terapi konservasi uterus pada wanita POP yang masih muda dengan keinginan untuk memiliki keturunan melalui operasi sakrohisteropeksi per abdominal.Ilustrasi Kasus: Seorang wanita 42 tahun, P2A0, datang dengan massa menonjol dari jalan lahir sejak 6 bulan. Dia masih menstruasi dan suaminya masih berharap memiliki anak. Pada pemeriksaan POP-Q didapatkan prolaps uterus derajat 4, sistokel derajat 3, dan rektokel derajat 3. Dia memutuskan konservasi uterus melalui prosedur sakro histeropeksi. Satu bulan setelah prosedur, pasien merasa puas dan tidak ada keluhan lagi.Diskusi: Sakro histeropeksi merupakan tindakan pembedahan yang menjanjikan dengan angka tidak ada kekambuhan pada tiga sampai lima tahun mencapai 90%. Penggunaan mesh berkaitan dengan risiko infeksi dan keluar mesh dari vagina. Angka rekurensi biasanya disebabkan oleh kelemahan dasar panggul dengan prevalensi 16,7%.Kesimpulan: Sakro histeropeksi perabdominam merupakan prosedur aman untuk POP wanita muda yang masih menginginkan adanya rahim.